Breastmilk Management Education on Knowledge and Breastfeeding Practices Among Working Mothers - Sukriani, Wahidah; Wahyuni, Seri (Sarana Ilmu Indonesia (salnesia), 2024)
One of the factors causing the failure of exclusive breastfeeding is working mothers. Previous research has stated that working others are 2,3 times less likely to provide breast milk compared to non-working mothers. This study aimed to analyze the influence of education on expressed breast milk management using pocket books on knowledge and breastfeeding among working mothers in Palangkaraya City. This research was a quasi-experimental study using pretest-posttest control group structure. This study?s sample include breastfeeding women who work in the working area of Palangkaraya City Public Health Center, with 30 participants in each group. The sample was selected using consecutive sampling technique. Statistical tests were performed using the chi-square test. Observation of expressed breast milk feeding was carried out one month after the mothers returned to work. This study result found significant differences in knowledge and breastfeeding practices between the intervention and control groups (p-value<0,05). Most of the mothers who were given the pocket book had good knowledge, while most of the mothers who used the KIA book had sufficient knowledge. Mothers who were given the pocket book were also more likely to provide expressed breast milk to their babies compared to mothers who used the KIA book. Health workers can provide education about expressed breast milk to working mothers using pocket books that are easy to carry, allowing mothers to read them anywhere and manage expressed breast milk at work to increase the achievement of exclusive breastfeeding.